Relative and Absolute Stellar Aberration (JOURNAL OF ADVANCES IN PHYSICS, 2023)
If we talk about Stellar Aberration, then we think of the form of Stellar Aberration that was first discovered and explained by Bradley. In addition to Bradley's Stellar Aberration, which can also be defined as Relative Stellar Aberration, we will define Absolute Stellar Aberration based on just one measurement. Here after we will refer to the Absolute Stellar Aberration as $ASA$. We will try to explain in a few words why it is necessary to measure and interpret Stellar Aberration in this way. Suppose we performed two measurements of the Doppler Effect within six months. If we don't know the results of those measurements, but only difference between them, then we cannot determine the radial velocities with which the observer moves with respect to the star. We will prove that similar reasoning can be applied in the case of Stellar Aberration as defined by Bradley. Knowing only the difference between the two measurements of the Stellar Aberration, we are not able to determine the transverse velocities the observer moves with respect to the line of sight, but only their difference. Using the results of $ASA$ measurements, we will determine a Reference Inertial Frame and after that derive formulas for Relative and Absolute Stellar Aberration.